A compact UWB bandpass filter with a notched band using a multistubs loaded resonator. Issue 1 (21st September 2016) - Zhang, Ting; Xiao, Fei; Bao, Jingfu; Tang, Xiaohong
Abstract: A novel multistubs loaded resonator (MSLR) is proposed in this article, which is constructed by several open‐ and short‐circuited stubs. The analysis shows that it is characterized by four resonant modes. Then, the MSLR is applied in the design of a compact ultra‐wideband (UWB) bandpass filter. The measured results show that its 3dB bandwidth can cover [3.0, 11.5] GHz, that is, 3 dB fractional bandwidth is 117%, and the return loss within the passband is greater than 15 dB. Especially, the roll‐off rate is higher than 33 dB/GHz and more than 40 dB harmonic suppression can be achieved up to 17 GHz. In order to suppress the interference of some undesired narrowband signal such as wireless local‐area network (WLAN) radio signal, a notched band is created for the UWB bandpass filter, which is realized by forming one stepped slot on each of the feedlines, respectively. The measured results show that a notched band with 2.01% fractional bandwidth at the center frequency of 5.85 GHz can be achieved and its suppression is about −19 dB.